1989
DOI: 10.2307/1389006
|View full text |Cite
|
Sign up to set email alerts
|

Alzheimer's Disease Victims: The “Unbecoming” of Self and the Normalization of Competence

Abstract: This study examines the importance of routinized practices for the self Alzheimer's disease victims are observed in their daily lives. The deterioration of self is discussed, followed by a discussion of routinized actions and normalization practices by caregivers that allow the patients to be seen as competent selves. Finally, the last remnants of the self in Alzhiemer's patients are discussed. The authors conclude that when the individual self undergoes an “unbecoming” process, due to the mental deterioration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
74
0
1

Year Published

1993
1993
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(82 citation statements)
references
References 3 publications
7
74
0
1
Order By: Relevance
“…'s ratings be so reliable, yet agree so little with those who know her best? In this regard her performance is consistent with clinical judgements that characterise late-stage Alzheimer's patients as lacking a sense of self (e.g., Cohen & Eisdorfer, 1986;Fontana & Smith, 1989;Orona, 1990;Ronch, 1996).…”
Section: Patients Suffering Varying Degrees Of Episodic Amnesiasupporting
confidence: 79%
“…'s ratings be so reliable, yet agree so little with those who know her best? In this regard her performance is consistent with clinical judgements that characterise late-stage Alzheimer's patients as lacking a sense of self (e.g., Cohen & Eisdorfer, 1986;Fontana & Smith, 1989;Orona, 1990;Ronch, 1996).…”
Section: Patients Suffering Varying Degrees Of Episodic Amnesiasupporting
confidence: 79%
“…There are some studies of Alzheimer's disease and other types of dementia where researchers have noted that relatives and caregivers reported that they often felt embarrassed by the behaviours of their ill family member (Greene et al 1982, Argyle et al 1985, Fontana and Smith 1989. Moreover, while there are not many studies which focus directly on the topic of Alzheimer's disease and stigma, there are a few exceptions (Schifflet andBlieszner 1988, Blum 1991).…”
Section: Courtesy Stigma and Alzheimer's Diseasementioning
confidence: 99%
“…Loss of self is a fundamental consequence of chronic illness (Charmaz 1983;Fontana and Smith 1989;Orona 1990Orona : 1254. Fontana and Smith (1989: 43-5) describe ftirther what aspects of selfhood remain after the deteriorating effects of Alzheimer's disease.…”
Section: Introductionmentioning
confidence: 99%